Secondary stroke prevention through patient education intervention on lifestyle risk factors: a review - Sowtali, Siti Noorkhairina; Harith, Sakinah; Mohamed, Che Rabiaah (School of Health Sciences, Universiti Sains Malaysia, 2013)
Stroke ranks top five causes of mortality in Malaysia with the rate of 8.3/100,000 population. Stroke are characterised by acute neurological deficits and mostly associated with vascular causes. Risk factors which contribute towards 90% of overall stroke are hypertension, unhealthy diet, physical inactivity, excessive alcohol intake, psychosocial stress, atria fibrillation, smoking, high cholesterol and diabetes. Thus, appropriate secondary stroke prevention is required in modifying these risk factors via educational intervention. The aim of this article is to provide a review of literature pertaining to the risk factors associated with stroke highlighting the lifestyle risk factors. Furthermore, this review will also discuss upon the importance of systematic patient education process and applying health promotion theories in lifestyle intervention. Various educational techniques nurses and other healthcare professional can adopt to address lifestyle behavioural changes following stroke will be discussed briefly in this paper.